Comparison of different phytoremediation strategies for acid mine drainage (AMD) - Rahman, R.A.; Wintoko, J.; Prasetya, A. (2022)
Acid Mine Drainage (AMD) is a severe environmental problem that results from mining industry activities around the world. Water pollution from acid mine drainage not only damages the quality of water and soil but also affects a sustainable environment such as plants and animals in a mining area. Mining water typically has acid with highly toxic heavy metal concentrations. Remediation is one of the technologies that can be used to reduce heavy metal pollutant water from mine drainage water. There were many researches about remediation in the past, but phytoremediation has attracted various researchers' attention. Phytoremediation is a remediation pollutants method using a plant as a media that has the advantages of being efficient, economical, and eco-friendly. The most significant important aspect for the successful phytoremediation method is a selection of the plant species. Aquatic plants have a high level of efficiency in reducing organic and inorganic pollutants in water. The efficiency of aquatic plants can be improved with innovative approaches. This review focuses on the comparison characteristic of aquatic plants in the phytoremediation method to reduce heavy metals in pollutant water. Comparison served to support innovations to improve efficiency phytoremediation application research challenge for acid mine drainage issues in the near future.